Effectiveness of Technical Training Interns in Skills Application in Nyeri County, Kenya - Waihura, E.; Kagema, J.; Kimiti, P. (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2019)
Technical, industrial, vocational and entrepreneurship training Institutions (TIVET) are a key component to provide the required human resource to achieve Kenya’s Vision 2030. This study sought to find out the effectiveness of technical training interns in skills application in Nyeri County, Kenya. The study sought to establish the industrial supervisors’ attitude towards competence of technical training interns in the work-place. The study was guided by Context, Input, Process and Product (CIPP) Theory. The study adopted a descriptive survey research design with a target population was 10 Heads of Applied Sciences Department, 45 supervisors from the companies within Aberdare’s Region that offers a technical and practical based internship to interns from technical training institutions. The sample used in the study comprised of 73 respondents comprising of 10 HODs and eight supervisors’. Purposive sampling was used to select the HODs and Supervisors’ for the study. The questionnaire and the interview guide were piloted to test for reliability and validity. The reliability coefficient for the TIVET Heads of Department Questionnaire was 0.767. Inferential and descriptive statistics was applied to analyse data with aid of SPSS computer program. The study established a mean of 1.62 and standard deviation of 0.774 to the statement. The findings show that the supervisors’ thought the TIVET curriculum was theoretical to some extent. 25% and 37.5% indicated that they strongly disagreed and disagreed respectively to the statement that TIVET curriculum was in line with the current technology in the country. The study concludes that technical and vocational education is the core driver for countries the world over to achieve envisaged steps in economic and technological development. Ensuring that curriculum of TIVET education be more practical based will make this education effective. The authors recommend that the attachment period should be extended to enhance the interns’ effectiveness and application of knowledge through hands-on experience in real production work.